Respuesta :
[tex] \frac{y}{3}-6=-8 [/tex]
add 6 to both sides
[tex] \frac{y}{3}-6+6=-8+6 [/tex]
[tex] \frac{y}{3}=-2 [/tex]
multiply both sides by 3
[tex] 3\frac{y}{3}=-2(3) [/tex]
[tex] y=-6 [/tex]
add 6 to both sides
[tex] \frac{y}{3}-6+6=-8+6 [/tex]
[tex] \frac{y}{3}=-2 [/tex]
multiply both sides by 3
[tex] 3\frac{y}{3}=-2(3) [/tex]
[tex] y=-6 [/tex]
You need to get y to 1. So multiply everything by 3. The equation you get is y-18=-24. You need to get y by itself so add 18 to both sides. The equation you get is y=-6. So the answer is y=-6. Hope this helps! ;)